Comparison of alternative gestational age assessment methods in a low resource setting: a retrospective study - Andrea Pietravalle; Silvia Spolverato; Luca Brasili; Francesco Cavallin; Valentina Gabrielli; Gaetano Azzimonti; Donald Micah Maziku; Dionis Erasto Leluko; Daniele Trevisanuto; Giovanni Putoto (BMC, 2022)
Abstract Background Accurate gestational age (GA) determination allows correct management of high-risk, complicated or post-date pregnancies and prevention or anticipation of prematurity related complications. Ultrasound measurement in the first trimester is the gold standard for GA determination. In low- and middle-income countries elevated costs, lack of skills and poor maternal access to health service limit the availability of prenatal ultrasonography, making it necessary to use alternative methods. This study compared three methods of GA determination: Last Normal Menstrual Period recall (LNMP), New Ballard Score (NBS) and New Ballard Score corrected for Birth Weight (NBS + BW) with the locally available standard (Ultrasound measurement in the third trimester) in a low-resource setting (Tosamaganga Council Designated Hospital, Iringa, Tanzania). Methods All data were retrospectively collected from hospital charts. Comparisons were performed using Bland Altman method. Results The analysis included 70 mother-newborn pairs. Median gestational age was 38 weeks (IQR 37-39) according to US. The mean difference between LNMP vs. US was 2.1 weeks (95% agreement limits − 3.5 to 7.7 weeks); NBS vs. US was 0.2 weeks (95% agreement limits − 3.7 to 4.1 weeks); NBS + BW vs. US was 1.2 weeks (95% agreement limits − 1.8 to 4.2 weeks). Conclusions In our setting, NBS + BW was the least biased method for GA determination as compared with the locally available standard. However, wide agreement bands suggested low accuracy for all three alternative methods. New evidence in the use of second/third trimester ultrasound suggests concentrating efforts and resources in further validating and implementing the use of late pregnancy biometry for gestational age dating in low and middle-income countries.